Identification of Key lncRNAs Associated With Atherosclerosis Progression Based on Public Datasets - Wang, Chuan-hui; Shi, Hui-hua; Chen, Lin-hui; Li, Xiao-li; Cao, Guo-liang; Hu, Xiao-feng (Frontiers in Genetics, 2019)
Atherosclerosis is one of the most common type of cardiovascular disease and the prime cause of mortality in the ageing population worldwide. However, the detail mechanisms and special biomarkers of atherosclerosis remained to be further investigated. Lately, long non-coding RNAs (lncRNAs) had attracted much more attention than other types of ncRNAs. In our work, we found and confirmed differently expressed lncRNAs and mRNAs in atherosclerosis by analyzing GSE28829. We performed the weighted gene co-expression network analysis (WGCNA) by analyzing GSE40231 to confirm highly correlated genes. Gene Ontology (GO) analysis were utilized to assess the potential functions of differential expressed lncRNAs in atherosclerosis. Co-expression networks were also constructed to confirm hub lncRNAs in atherosclerosis. A total of 5784 mRNAs and 654 lncRNAs were found to be dysregulated in the progression of atherosclerosis. A total of 15 lncRNA-mRNA co-expression modules were identified in this study based on WGCNA analysis. Moreover, a few lncRNAs, such as ZFAS1, LOC100506730, LOC100506691, DOCK9-AS2, RP11-6I2.3, LOC100130219, were confirmed as important lncRNAs in atherosclerosis. Taken together, bioinformatics analysis revealed these lncRNAs were involved in regulating leukotriene biosynthetic process, gene expression, actin filament organization, t-circle formation, antigen processing and presentation, interferon-gamma-mediated signaling pathway, and activation of GTPase activity. We believed that this study would provide potential novel therapeutic and prognostic targets for atherosclerosis.